Anmeldelser - Kongsted, Ole (Danish Yearbook of Musicology, 2000)
Review of: Mara R. Wade: Triumphus Nuptialis Danicus. German Court Culture and Denmark. The “Great Wedding” of 1634 (Wolfenbütteler Arbeiten zur Barockforschung 27). Harrasowitz Verlag, Wiesbaden 1996.